Ultra-high dispersion of graphene in polymer composite via solvent free fabrication and functionalization - Noh, Ye Ji; Joh, Han-Ik; Yu, Jaesang; Hwang, Soon Hyoun; Lee, Sungho; Lee, Cheol Ho; Kim, Seong Yun; Youn, Jae Ryoun (NATURE PUBLISHING GROUP, 2015)
The drying process of graphene-polymer composites fabricated by solution-processing for excellent dispersion is time consuming and suffers from a restacking problem. Here, we have developed an innovative method to fabricate polymer composites with well dispersed graphene particles in the matrix resin by using solvent free powder mixing and in-situ polymerization of a low viscosity oligomer resin. We also prepared composites filled with up to 20 wt% of graphene particles by the solvent free process while maintaining a high degree of dispersion. The electrical conductivity of the composite, one of the most significant properties affected by the dispersion, was consistent with the theoretically obtained effective electrical conductivity based on the mean field micromechanical analysis with the Mori-Tanaka model assuming ideal dispersion. It can be confirmed by looking at the statistical results of the filler-to-filler distance obtained from the digital processing of the fracture surface images that the various oxygenated functional groups of graphene oxide can help improve the dispersion of the filler and that the introduction of large phenyl groups to the graphene basal plane has a positive effect on the dispersion.
Keywords: EXFOLIATED GRAPHITE OXIDE; IN-SITU POLYMERIZATION; THERMAL-CONDUCTIVITY; ENHANCED DISPERSION; LARGE-AREA; REDUCTION; CARBON; NANOCOMPOSITES; FILMS; FIELD